Currency account dynamics and real effective exchange rate : the Jamaican experience - Henry, Chandar ([Caribbean Centre for Monetary Studies] [St. Augustine]TT, 2002)
Explores the dynamics of Jamaica's current account and the real effective exchange rate (REER). Investigates short-run and long-run considerations. Discovers that the influence of fluctuations in the REER on some components of the current account was negligible.